2010
DOI: 10.3382/ps.2009-00547
|View full text |Cite
|
Sign up to set email alerts
|

The effect of glucagon-like peptide 2 injection on performance, small intestinal morphology, and nutrient transporter expression of stressed broiler chickens

Abstract: An experiment was conducted to determine the effect of injecting glucagon-like peptide 2 (GLP-2) on the small intestinal weight, morphology, and nutrient transporter expression in pharmacologically stressed broiler chickens. A total of 144 seven-day-old birds were fed either a basal diet (CTRL) or a basal diet plus 30 mg of corticosterone (CORT)/kg of diet for a total of 14 d. Half of the birds from each group were injected daily with GLP-2 (6.7 nmol/kg of BW) or saline for 14 d. The average final BW, ADG, ADF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 50 publications
3
43
1
Order By: Relevance
“…Its receptor (GLP-2R) is localized on distinct subpopulations of gut endocrine cells in the stomach, small intestine, and colon but also on subepithelial myofibroblasts (67,68). Hu et al showed a beneficial effect of intravenous GLP-2 injection in broilers on growth performance, intestinal morphology, villus height, and crypt cell proliferation (69).…”
Section: Discussionmentioning
confidence: 99%
“…Its receptor (GLP-2R) is localized on distinct subpopulations of gut endocrine cells in the stomach, small intestine, and colon but also on subepithelial myofibroblasts (67,68). Hu et al showed a beneficial effect of intravenous GLP-2 injection in broilers on growth performance, intestinal morphology, villus height, and crypt cell proliferation (69).…”
Section: Discussionmentioning
confidence: 99%
“…• Decreased skeletal muscle weight (Yuan et al, 2008;Song et al, 2011) • Increased protein degradation as indicated by increases in the concentrations of 3-methyl histidine in both pectoralis and femoris muscles (Dong et al, 2007) • Increases muscle proteolysis (Gao et al, 2008) • Reduced skeletal protein synthesis as indicated by the RNA:protein ratio (Dong et al, 2007) Decreasing the growth of the small intestine in chickens although the effect is of a small magnitude than that with overall growth as weight of the small intestine relative to body weight is increased (Hu et al, 2010) • Increases expression of myostatin (Song et al, 2011).…”
Section: Corticosterone and Growthmentioning
confidence: 99%
“…• Increasing expression sodium and glucose co-transporter 1 (SGLT-1 vitamin Ddependent calcium-binding protein-28,000 molecular weight (CaBP-D28k), and peptide transporter 1 (PepT-1) mRNA in the duodenum (Hu et al, 2010) • Increasing expression of genes related to obesity in the chicken hypothalamus including brain-derived neurotrophic factor (BDNF), neuropeptide Y and agouti-related protein (AGRP) (Byerly et al, 2009) • Depressing adenosine deaminase activity in all regions of the chicken gastro-intestinal tract except the proventriculus (Bhattacharjee et al, 2009).…”
Section: Other Metabolic Effects Of Corticosteronementioning
confidence: 99%
See 2 more Smart Citations